2012
DOI: 10.3856/vol40-issue1-fulltext-13
|View full text |Cite
|
Sign up to set email alerts
|

Territorial hypothesis predicts the trade off between reproductive opportunities and parental care in three species of damselfishes (Pomacentridae: Actinopterygii)

Abstract: ABSTRACT. Paternal care is rare in most animals, but common in fishes, including Pomacentridae. One way of explaining it is through the territorial hypothesis, which predicts that paternal care may evolve when caring for a territory with eggs will not cost more than territories without eggs. Here we describe the reproductive behavior of three pomacentrids from São Paulo, Brazil, and evaluate if the territorial hypothesis explains their behavioral variation through five predictions. We checked if females have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…This outcome suggests that the duration between gamete release and the appearance of recruits >2 cm is about 2 months. This result sounds plausible, given the fact that larval dispersion in most pomacentrids is reduced (10-24 days, Thorrold andMilicich 1990, Nemeth 2005), and that males guard fertilized eggs for only a few weeks (Thresher 1984, Asoh and Yoshikawa 2002, Bessa and Sabino 2012. Some authors have suggested that some variability in the time of recruitment may arise as a result of several spawning acts, or that larval duration varies due to environmental uncertainty (Robertson 1990, Thorrold andMilicich 1990).…”
Section: Discussionmentioning
confidence: 95%
“…This outcome suggests that the duration between gamete release and the appearance of recruits >2 cm is about 2 months. This result sounds plausible, given the fact that larval dispersion in most pomacentrids is reduced (10-24 days, Thorrold andMilicich 1990, Nemeth 2005), and that males guard fertilized eggs for only a few weeks (Thresher 1984, Asoh and Yoshikawa 2002, Bessa and Sabino 2012. Some authors have suggested that some variability in the time of recruitment may arise as a result of several spawning acts, or that larval duration varies due to environmental uncertainty (Robertson 1990, Thorrold andMilicich 1990).…”
Section: Discussionmentioning
confidence: 95%
“…The Pomacentridae A. saxatilis prefers substrates covered by zoanthids probably because this habitat offers a safety place for oviposition and predation avoidance. This species presents similar reproductive traits to S. fuscus such as mating in couples, demersal adhesives eggs attached to rocks, and male parental care (Bessa & Sabino 2012). Habitats with predominance of zoanthids are more structuraly complex, offering more shelter places (Ferreira et al 2004;Quadros et al 2019).…”
Section: April Marchmentioning
confidence: 96%
“…That was observed in the ocellated wrasse ( Symphodus ocellatus , Labridae), whose nesting males were less attacked than non‐nesting males (Stiver et al, 2019). Males of two southern Atlantic pomacentrids (the sergeant major ( Abudefduf saxatilis , Pomacentridae) and the dusky damselfish ( Stegastes fuscus , Pomacentridae)) holding nest sites perform much less defensive behaviours than individuals without one (Bessa & Sabino, 2012). Thus, other benefits of nesting in fish may be social rank signalling, reducing time and energy spent in agonistic contests.…”
Section: Nest Types and Functionsmentioning
confidence: 99%
“…Turtle‐headed sea snakes can use olfactory cues to locate nests and prey on small fish and eggs placed in large areas of coral reefs in New Caledonia (Shine et al, 2004). The purple eggs of the sergeant major Abudefduf saxatilis are easily found by predators, hence nesting males spend more time averting egg predators than Chromis multilineata (Pomacentridae), another pomacentrid that conceals eggs amid algae (Bessa & Sabino, 2012). A cooperative interaction between Stegastes fuscus damsels and the dusky grouper ( Epinephelus marginatus , Serranidae) was reported, in which the damsel benefits from sharing its territory with a grouper because this serranid feeds on egg predators attracted by the nest (Bessa, 2011).…”
Section: Costs and Constraints Of Nestingmentioning
confidence: 99%
See 1 more Smart Citation